Fantastic Daisy Artichoke - Quentin Blake (London, United Kingdom Random House Children's Publishers UK, 2001)
Meet Fantastic Daisy Artichoke. She's got three fat cats we like to stroke and a pond in which she likes to soak...She isn't quite like other folk!
Keywords: Read Aloud -- Read Aloud